Tracheobronchial Foreign Bodies in Children: The Role of Emergency Rigid Bronchoscopy - Aram Baram MD, MRCSEd, FACS, AFSCTS; Hewa Sherzad MD; Sara Saeed MD, FKBMS; Fahmi H. Kakamad MD; Adnan M. H. Hamawandi MD, CABP (SAGE Publishing, 2017)
Foreign body aspiration (FBA) is a common and lethal accident in the pediatric age group. It requires early recognition and treatment by rigid bronchoscopy to avoid fatal outcomes. Objective. The aim of this study was to study the pattern of FBA in the tracheobronchial tree as well as the success rate of rigid bronchoscopy in children admitted to a single center and to analyze the relationship of the type of foreign body (FB) with patients' age, presentation, and complications. Methods. A retrospective cross-sectional study of FBA was conducted in children in the Sulaimani/Kurdistan region, Iraq, admitted to the emergency teaching hospital of the University of Sulaimani from January 2014 to March 2016. Result. Data of 83 patients between 6 months and 15 years old were studied. The most affected was the 1- to 5-year-old group. There was a slight female predominance (male to female ratio 0.93:1). The most common FB was sunflower seed (49.4%). History of choking was present in 92.8% of patients; 55.4% had normal air entry, and 37.3% had no added sound on chest auscultation. Normal chest X-ray (CXR) was found in 40% of patients. The most common site was the right bronchial tree (39.8%). Two patients needed mechanical ventilation; both of them died. There was a significant relationship between the type of FB ( P = .013, .000, respectively). Conclusion. Medical history is the most important factor for reaching the diagnosis; bronchoscopy is mandatory if choking was witnessed, even if examination and CXR are normal. Organic material causes more local reaction than nonorganic material.